Modelling Temperature Profles in Food Waste Composting: Monod Kinetics Under Varied Aeration Conditions - Lai, Jia Chi; Then, Yi Lung; Hwang, Siaw San (Springer, 2025)
Composting has become a widely adopted alternative to landflling for food waste management, ofering signifcant environmental benefts by reducing waste and mitigating climate change. This study focuses on enhancing the efciency of food waste composting by applying mathematical modelling to better understand the underlying biological and physiochemical mechanisms. First-order and Monod-type kinetic were incorporated to predict temperature variations in food waste composting under diferent aeration conditions. These models were solved and validated against experimental data to assess their predictive accuracy. In the composting process involved intermittent aeration, the modelled temperature profles showed good agreement with experimental data, with mean temperature diferences of 1.99 °C for the frst-order and 2.16 °C for the Monod-type kinetic. Monod-type kinetic provided more consistent predictions, achieving a lower relative root mean square error (rRMSE) of 8.03%, while the frst-order model exhibited larger temperature fuctuation. Notably, experimental data indicated a second peak in temperature on the seventh day, likely due to delayed microbial activity, a trend not fully captured by either model. In the composting process with continuous aeration, the Monod-type kinetic demonstrated better predictive performance at higher aeration rates, with an rRMSE of 10.82%. However, both models struggled to accurately predict complex temperature fuctuations at lower aeration rates. The results suggest that Monod-type kinetic provides superior prediction accuracy due to its ability to account for the interactions between multiple substrates and microorganisms. This study highlights the value of mathematical modelling in understanding and optimizing food waste composting processes. The fndings ofer practical insights for improving composting efciency and operational management, ultimately contributing to reduced environmental impacts from food waste.